SPRAYED CLAY TECHNOLOGY FOR THE DEEP REPOSITORY OF HIGH-LEVEL RADIOACTIVE WASTE - Lucie Hausmannová; Radek Vašíček; Jiří Šťástka (Rudarsko-geološko-naftni Zbornik, 2012)
The sealing barrier will play very important role in the Czech disposal concept of high level radioactive waste. It follows Swedish SKB3 design where granitic rock environment will host the repository. Swelling clay based materials as the most favorable for sealing purposes were selected. Such clays must fulfill certain requirements (e.g. on swelling properties, hydraulic conductivity or plasticity) and must be stable for thousands of years. Better sealing behavior is obtained when the clay is compacted. Technology of the seal construction can vary according to its target dry density. Very high dry density is needed for buffer (sealing around entire canister with radioactive waste). Less strict requirements are on material backfilling the access galleries. It allows compaction to lower dry density than in case of buffer. One of potential technology for backfilling is to compact clay layers in most of the gallery profile by common compaction machines (rollers etc.) and to spray clay into the uppermost part afterwards. The paper introduces the research works on sprayed clay technology performed at the Centre of Experimental Geotechnics of the Czech Technical University in Prague. Large scale in situ demonstration of filling of short drift in the Josef Gallery is also mentioned.